THE CORRELATION BETWEEN SELF-CONFIDENCE AND SPEAKING ACHIVEMENT OF ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 AIR SUGIHAN - Sherly Marliasari; Deni Endah Pratiwi; Sri Hartati (Politeknik Negeri Sriwijaya, 2022)
The title of this article is “The Correlation between Self-Confidence and Speaking Achievement of Eleventh Grade Students of SMA Negeri 1 Air Sugihan”. The problem of this research was “Was there any significant correlation between self-confidence and speaking achievement of the eleventh grade students of SMA Negeri 1 Air Sugihan?” the objective of this research was “to find out whether or not there is significant correlation between self-confidence and speaking achievement of eleventh grade students of SMA Negeri 1 Air Sugihan”. The participant of this research was eleventh grade students of SMA Negeri 1 Air Sugihan. The sample of this research was 52 students. The data were collected through a ready-made questionnaire and speaking test.The result of the test was analyzed by using Pearson Product Moment Correlation. Based on the data analyses (r-obtained=0.1.000) was higher than (r-table=237). It means that it has a significant correlation between self-confidence and speaking achievement of Eleventh Grade Students’ of SMA Negeri 1 Air Sugihan. Keywords: self-confidence and speaking achievement